Tinjauan Literatur : Penerapan Sistem Informasi Kesehatan di Puskesmas di Indonesia - Hanafi, Syahida Tahniah; Panjaitan, Wiranti Utami; Ramadhan, Ahmad Rezeki; Purba, Sri Hajijah (Yayasan Sagita Akademia Maju, 2025)
This research applies the implementation of the Health Information System in Indonesian Community Health Centers, with a focus on the challenges and solutions faced. Through a literature review of scientific literature from 2018 to 2024, this research found that Health Information Systems make a significant contribution in improving the efficiency of data management and health services. However, its implementation is hampered by limited workforce, inadequate infrastructure, network disruption, and lack of technological understanding. To overcome this problem, research recommends increasing training for workers, developing infrastructure, and better integrating systems to maximize the use of Health Information Systems in Community Health Centers.